An ionospheric scintillation index derived from dual-frequency Doppler measurements released by geodetic GNSS receivers operating at 1 Hz - Luo, Xiaomin (2023)
Doppler measurements are immune to cycle slips, which offers great potential for constructing the ionospheric scintillation indexes. This study proposes a new scintillation index referred to as Doppler Index (DI) derived from dual-frequency Doppler measurements released by geodetic receivers operating at 1 Hz. The reliability of DI is compared with the dedicated scintillation indexes S4 and σφ outputted by the ionospheric scintillation monitoring receivers (ISMRs) as well as the indexes ROTI and S4c derived from geodetic GNSS receivers. Experimental results suggest that there is strong correlation between DI and the common scintillation indexes S4 , σφ , and ROTI . The statistics indicate that the mean values of correlation coefficients between DI and S4 / σφ are around 0.6–0.8 based on three ISMR stations data located at low, middle, and high latitudes. Using different types of geodetic GNSS receivers (Septentrio, Javad, Leica, and Trimble) data, the mean values of correlation coefficients between DI and ROTI can reach around 0.9. In addition, due to the different tracking technologies and locations for the different receiver types, the features of scintillation occurrence thresholds based on DI are also analyzed in this study. Statistical results suggest that for the Septentrio, Javad, Leica, and Trimble receivers, the μ+ 3 σ can be used as the threshold of DI in ionospheric scintillation monitoring.